2020
DOI: 10.1002/ange.202007651
|View full text |Cite
|
Sign up to set email alerts
|

Formyl MIDA Boronate: C1 Building Block Enables Straightforward Access to α‐Functionalized Organoboron Derivatives

Abstract: Formyl MIDA boronate has been known to be an elusive type of acylboronate that has not been obtained to date. In this work, an approach to the one‐pot preparation and chemical transformations of formyl MIDA boronate were developed to provide new types of α‐functionalized organoboron compounds. Among them are acylboronate reagents which present boron‐substituted analogues of ynones and β‐dicarbonyl compounds. The developed synthetic procedures, utilizing formyl MIDA boronate, are tolerant to diverse functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Note added in proof: Since the submission of this Minireview,G rygorenko and co-workers reported the synthesis of formyl MIDAb oronate.T reatment of this building Angewandte block with organotitanium reagents followed by Dess Martin/ Swern oxidation produced alkynyl acylboronates. [63]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note added in proof: Since the submission of this Minireview,G rygorenko and co-workers reported the synthesis of formyl MIDAb oronate.T reatment of this building Angewandte block with organotitanium reagents followed by Dess Martin/ Swern oxidation produced alkynyl acylboronates. [63]…”
Section: Discussionmentioning
confidence: 99%
“…Minireviews block with organotitanium reagents followed by Dess Martin/ Swern oxidation produced alkynyl acylboronates. [63]…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Kurzaufsätze block with organotitanium reagents followed by Dess Martin/ Swern oxidation produced alkynyl acylboronates. [63]…”
Section: Angewandte Chemiementioning
confidence: 99%